ANALISIS PERILAKU KEPEMIMPINAN PEREMPUAN DALAM PENGELOLAAN PROGRAM STUDI TERINTEGRASI PONDOK PESANTREN - Ahmad Zarkasyi (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
This article aims to describe the analysis of women's leadership behavior in managing the integrated Islamic boarding school study program at the Miftahul Ulum Islamic College, Lumajang Regency. This research utilizes a qualitative approach to investigate aspects that exist in the natural environment, and attempts to interpret these phenomena. Data collection techniques were carried out by means of observation, interviews and documentation studies. In this research, researchers used several stages of data analysis, namely the condensation stage, data presentation stage, making temporary conclusions and verification activities. The research results concluded; women's leadership behavior in managing study programs that are integrated with the Islamic boarding school system at STAI Miftahul Ulum Lumajang are; 1) Dividing tasks according to the team's abilities and in accordance with the detailed job description so as to achieve success in achieving institutional goals; 2) Establishing regular communication and meetings, namely by holding regular discussion meetings with staff, lecturers and students. The meeting is aimed at strengthening ties, to express complaints or resolve existing problems; 3) Inspire the results that have been achieved with the hope that the academic community can increase their work enthusiasm in achieving institutional goals.